2019
DOI: 10.1016/j.ejphar.2018.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying select chemotherapeutic-agent-induced neuroinflammation and subsequent neurodegeneration

Abstract: This review demonstrates the importance of uncovering the mechanisms that underlie chemotherapy-induced neuroinflammation. It builds upon the well-established connection between chemotherapeutic-agents and neurotoxicity along with widespread peripheral toxicities. This article summarises the major studies which have linked chemotherapyinduced neurodegeneration with direct evidence of neuroinflammation. Cancer and chemotherapy-related adverse effects impact a large proportion of the population. A better underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 81 publications
(96 reference statements)
0
18
0
Order By: Relevance
“…This hypothetical compensation in the brain might have implications for traditional perspectives of the role of the brain in pain, such as how neurotoxic chemotherapy might cause a reduction in descending inhibition of pain (e.g., according to Gate Control Theory Melzack and Wall, 1965). For completeness, these hypothetical changes in the brain would be concurrent with other effects of chemotherapy such as neuroinflammation (McLeary et al, 2019), which sensitizes neurons and causes hyperactivity (Vezzani and Viviani, 2015).…”
Section: Overall Discussionmentioning
confidence: 97%
“…This hypothetical compensation in the brain might have implications for traditional perspectives of the role of the brain in pain, such as how neurotoxic chemotherapy might cause a reduction in descending inhibition of pain (e.g., according to Gate Control Theory Melzack and Wall, 1965). For completeness, these hypothetical changes in the brain would be concurrent with other effects of chemotherapy such as neuroinflammation (McLeary et al, 2019), which sensitizes neurons and causes hyperactivity (Vezzani and Viviani, 2015).…”
Section: Overall Discussionmentioning
confidence: 97%
“…Many chemotherapeutic agents invariably cause peripheral neurotoxicity, leading to permanent neuronal dysfunction [75][76][77][78][79] . Under conditions of denervation, Schwann cells become strongly susceptible to chemotoxicity 80 .…”
Section: Loss Of Sarm1 Protects Schwann Cells From Chemical Toxinsmentioning
confidence: 99%
“…Reciprocal and multidirectional effects of cell death, vascular activation, tumour-secreted factors, and therapy-induced responses, such as senescence, promote a widespread state of inflammation [134]. The effects of chemotherapy on intestinal epithelium, an inevitable target due to its high turnover rate, results in massive endotoxin release from gut microflora into circulation [135]. Inflammatory mediators, in turn, further contribute to microvascular remodelling, activation and increased permeability, perpetuating the cycle of vascular pathology, cardiovascular disease and oedema [136], as well as affecting the response to treatment [137] and potential for relapse [99].…”
Section: Unintended Casualtiesmentioning
confidence: 99%
“…Memory loss, disorganized thoughts, difficulty concentrating, and declines in recall and processing speed are seen in up to 80% of chemotherapy patients. While generally 35% of these patients report symptoms for years after completion of treatment [135], the proportion of breast cancer patients reporting long-term effects is almost twice that, nearing 60%, particularly in those treated with doxorubicin and/or cyclophosphamide [131,138]. A recent study has shown that these effects persist for 20 years after treatment, and those with lower cognitive function had associated higher levels of inflammatory markers [140].…”
Section: Unintended Casualtiesmentioning
confidence: 99%
See 1 more Smart Citation